2010
DOI: 10.1016/j.jfms.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Development of an in vitro model of feline cartilage degradation

Abstract: Osteoarthritis is the most common arthropathy of mammalian species including cats. Cartilage degradation is central to the disorder and here we present, for the first time, an in vitro model of feline cartilage degradation which will be useful for further studies in this target species. Feline articular cartilage explant cultures were maintained for 28 days and in the presence of oncostatin M with and without interleukin (IL)-17, tumour necrosis factor (TNF), IL-1alpha, or IL-1beta. Media samples and digested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This differs from many reported explant cultures that required the use of 5% CO 2 incubators or other complex gaseous parameters. 10,16 The relative simplicity of the set-up in terms of apparatus is an important consideration that should facilitate widespread use of the technology. With minor alterations to the device, we have already demonstrated that liver and cardiac tissues of similar size to the malignant biopsies can be maintained and studied; the latter being electrically stimulated.…”
Section: Discussionmentioning
confidence: 99%
“…This differs from many reported explant cultures that required the use of 5% CO 2 incubators or other complex gaseous parameters. 10,16 The relative simplicity of the set-up in terms of apparatus is an important consideration that should facilitate widespread use of the technology. With minor alterations to the device, we have already demonstrated that liver and cardiac tissues of similar size to the malignant biopsies can be maintained and studied; the latter being electrically stimulated.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, reliable and predictive in vitro models of AC tissues in healthy and OA conditions play a critical role in advancing the understanding of the physiology, biology, and pathological progression of OA, and will contribute hugely to the development of novel regenerative treatments for OA ( Grenier et al, 2014 ; Johnson et al, 2016 ). A variety of proinflammatory cytokines are commonly used to induce the ECM degradation seen in human OA which involves factors i.e., interleukins (IL-1α, IL-1β, IL-6, IL-8, IL-9) and tumour necrosis factor (TNF-α) ( Gabriel et al, 2010 ; Novakofski et al, 2012 ; Sylvester et al, 2012 ). Amongst them IL-1β, TNF-α and IL-6 are the three cytokines mostly induced in OA pathogenesis and possess a synergic effect: (i) IL-1β, which was found to inhibit Coll II and proteoglycans (PGs) and stimulate the production of MMP1,3,13, (ii) IL-6 to activate NF-kB pathway and downregulate the enzymatic antioxidant defenses in chondrocytes with mitochondria; (iii) TNF-α, which can activate the NF-kB pathway, increase the expression of MMPs, inhibit anabolic molecules, and stimulate chondrocytes apoptosis ( Fan et al, 2007 ; Calich et al, 2010 ; Meliconi et al, 2013 ; Löfgren et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…[16] Also, explants have been used as in vitro models, but their low availability and cell death at the tissue cut edges are noticeable disadvantages. [17] The development of 3D biomimetic models, providing an environment emulating the native one and giving cells with appropriate structure and force, allows to study cell-cell and cell-ECM interactions, overcoming the limitation of 2D models. The homeostasis of both AC and SB tissues is influenced by biological factors and signaling molecules able to cross the demarcation zone between the tissues.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] Also, explants have been used as in vitro models, but their low availability and cell death at the tissue cut edges are noticeable disadvantages. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%